2006
DOI: 10.1186/1471-2458-6-237
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HCV seropositivity among familial contacts of HCV positive patients

Abstract: Background: Determinants of intrafamilial HCV transmission are still being debated. The aim of this study is to investigate the correlates of HCV seropositivity among familial contacts of HCV positive patients in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
15
1
1
Order By: Relevance
“…Our prevalence is found to be higher than some others, for example the studies done by Mahmoud et al, Tibbs et al, La Torre et al and Sood et al, where the prevalence was 13.7%, 16%, 8.9% and 16%, respectively [21][22][23][24] . This noted difference may be attributed to the nonsimilar cultures and behavioral patterns of the studied populations, as well as from translocation from rural to urban areas.…”
Section: Discussioncontrasting
confidence: 56%
“…Our prevalence is found to be higher than some others, for example the studies done by Mahmoud et al, Tibbs et al, La Torre et al and Sood et al, where the prevalence was 13.7%, 16%, 8.9% and 16%, respectively [21][22][23][24] . This noted difference may be attributed to the nonsimilar cultures and behavioral patterns of the studied populations, as well as from translocation from rural to urban areas.…”
Section: Discussioncontrasting
confidence: 56%
“…In some studies, the length of the marriage18 40 49 50 was demonstrated as a risk factor for serum positivity, while in other studies33 47 48 such datum was not confirmed. The study by Vandelli51 excluded the intrafamilial transmission in the couples followed up for a 10-year average period.…”
Section: Discussionmentioning
confidence: 94%
“…Eighteen studies were thereafter excluded: one was a review on HCV epidemiology in childhood, five investigated risk factors for acquiring infection in general, three regarded other hepatic viruses, two evaluated cancer and cirrhosis in HCV patients, six focused on groups of patients other than households and one was about antiviral development. Thus, 9 studies were selected18 28–35 but, overall, 25 studies about HCV intrafamilial transmission in Italy were finally chosen18 28–51 because of the reading of the references of the same nine studies. All the studies were cross-sectional and written in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at least 50% of all HCV-positive patients do not have a clear history of parenteral or other risk factors 5. In areas with a high prevalence, intrafamilial transmission is suggested to play an important role.…”
Section: Introductionmentioning
confidence: 99%